Implementation Of The C4.5 Algorithm For Recruitment Of E-Sports Team Members - Akhmad Efendi; Anggit Dwi Hartanto (CCIT (Creative Communication and Innovative Technology) Journal, 2020)
Fenomena E-Sport in an increasingly fast-paced world, creating a global culture ranging from international E-Sport tournaments to the birth of management that houses the competing E-Sport teams to be the best. E-Sport teams need players or gamers who have high skills, but it is not only the skill level of a player that determines the success of an E-Sport team in a tournament, there are other factors that determine the success of an E-Sport team, where factors this can be used in determining the decision to recruit players or gamers to become members of the E-Sport team. Decision support systems (DSS) is one of the systems that can be relied upon as a method to assist an organization or E-sports team management in assisting the decision-making process. One method that can be used in DSS is to use the Decision Tree C4.5 Algorithm. The solution technique is to use entropy and information gain for the expansion of decision trees. C4.5 algorithm is a decision tree-based method. In the C4.5 algorithm, the selection of attributes is done using Gain, Ratio, by finding the Entropy value. C4.5 algorithm can provide effective results in supporting a decision